Advancing in hydraulic analysis: Integration of optimisation methods and renewable energy sources - Suchánková, Marcela; Fialová, Simona; Pochylý, František (My University, 2025)
Many freely available software programs for hydraulic analysis often fail to deliver adequate optimization outputs for topology design or may not be available at all. The novel software currently in development presents several innovative features compared to commercial programs. It integrates conventional distribution network elements alongside new components that aim to maximize the use of renewable energy. The components under review consist of a multifunctional water tower designed to utilize a wind turbine together with a ball reverse screw and a piston pump. This configuration ensures the full utilization of wind energy for pumping water to the upper reservoir of the tower. Another component is the irrigation zone, where the goal was to simplify modelling from the user's perspective. Additionally, the PV zone supplies users with data regarding energy generation for a specified area and the configuration of PV panels. These elements are mathematically integrated with the hydraulic analysis. The results indicate pressure values at nodes, flow through pipes, user recommendations, and data on specific areas like solar and wind power generation. After the calculations, users receive options for optimizing the distribution network. These options entail selecting the appropriate pipe diameter related to cost, as well as the optimal placement of tanks and water towers, ensuring suitable pressure at nodes (to prevent cavitation or excessive pressures), minimizing hydraulic losses, and reducing irrigation water costs (the application primarily focuses on irrigation in urban and natural landscapes). This paper further explored the selected options for optimizing the distribution network and the associated elements.

Many freely available software programs for hydraulic analysis often fail to deliver adequate optimization outputs for topology design or may not be available at all. The novel software currently in development presents several innovative features compared to commercial programs. It integrates conventional distribution network elements alongside new components that aim to maximize the use of renewable energy. The components under review consist of a multifunctional water tower designed to utilize a wind turbine together with a ball reverse screw and a piston pump. This configuration ensures the full utilization of wind energy for pumping water to the upper reservoir of the tower. Another component is the irrigation zone, where the goal was to simplify modelling from the user's perspective. Additionally, the PV zone supplies users with data regarding energy generation for a specified area and the configuration of PV panels. These elements are mathematically integrated with the hydraulic analysis. The results indicate pressure values at nodes, flow through pipes, user recommendations, and data on specific areas like solar and wind power generation. After the calculations, users receive options for optimizing the distribution network. These options entail selecting the appropriate pipe diameter related to cost, as well as the optimal placement of tanks and water towers, ensuring suitable pressure at nodes (to prevent cavitation or excessive pressures), minimizing hydraulic losses, and reducing irrigation water costs (the application primarily focuses on irrigation in urban and natural landscapes). This paper further explored the selected options for optimizing the distribution network and the associated elements.
Advancing in hydraulic analysis: Integration of optimisation methods and renewable energy sources
Keywords: optimization; irrigation; water cost; wind power; solar power; hydraulic analysis; renewable energy; urban smart irrigation; optimization; irrigation; water cost; wind power; solar power; hydraulic analysis; renewable energy; urban smart irrigation